Selected Sustainability Indicators and Performance Rankings at The Herbal Medicine Company - Triana, Masrifah; Rifin, Amzul; Suprehatin (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Sustainability means not only the sustainable use of natural resources but also core values in the areas of human rights (HAM), employment, and inclusive business. Supply chain management performance assessment has a direct influence on sustainability performance. Compliance, monitoring, and auditing have a direct influence on improving performance, minimizing risk, and selecting suppliers to achieve Sustainable Supply Chain Management (SSCM). The research was carried out at the herbal medicine company PT. Sido Muncul Herbal Medicine and Pharmaceutical Industry Tbk.Purpose: This research aims to select indicators, determine priorities for sustainability aspects, and select alternative SSCM performance measuresDesign/methodology/approach: the Analytical Hierarchy Process (AHP) method.Findings/Result: The top priority sustainability indicators for each sustainability aspect are net profit, employee training and development, occupational safety and health management systems, partnerships, environmental management systems, ISO 14001 certification, and certified quality management and food safety. By knowing the main indicators and priority aspects of sustainability; a manager can implement relevant and profitable SSCM activities and manage trade-offs between conflicting objectives by ensuring that profitability, environmental sustainability, and social sustainability of society can be implemented effectively, efficiently, and sustainably.Conclusion: As a result, it can be concluded that the implementation of sustainability aspects in SIDO requires models, processes, and practices adapted to planning, production, and control. Sustainability practices are no longer considered complementary but standard business activities, so they need to be integrated. The wider the integration of sustainability into the company's business, the wider the level of integration across the enterprise's operations.Originality/value (State of the art): SCM is a field that is concerned with sustainability performance related to its activities in generating pollution, waste, and environmental footprint. Although there is an increasing conceptual development of SCM practices and has received much attention, previous research has only focused on selecting priority SSCM practices that are most relevant to improving SSCM performance and has not linked sustainability to supply chain drivers and alternative performance measures to improve sustainability performance. In this research was conducted identifying successful supply chain practices in the context of the large corporate culture, has been listed on the Jakarta Stock Exchange, has gone global, and its products are widely used by the public, compliance with government regulations, and international standards by expanding aspects of social sustainability to K3, human resources, community, and product integrity which were not found in previous studies. Keywords: Analytical Hierarchy Process, corporate sustainability indicators, sustainability practices, performance measurements, PT. Sido Muncul Tbk